Pengaruh Metode Penemuan Terbimbing dengan Metode Ekspositori dalam Pembelajaran Matematika pada Siswa Kelas X SMA Negeri 1 Wotu - Syamsu Alam; Patmaniar (Almeera Education, 2023)
This study aims at examining (1) the difference of learning results between student who taught by guided discovery method and the ones taught by expository method, (2) the interaction between the method and students’ learning motivation toward students’ learning achievement. The population of this study was grade X students of SMAN 1 Wotu. As the sample, two classes were taken with 66 students which was divided into two groups, namely the experiment class and the control class. Grade XA with 33 students was the experiment class with guided discovery method; whereas, grade XB with 33 students was control calls with expository method. Sample was selected by using simple random sampling technique. Data were collected by using test of learning achievement and questionnaire of learning motivation. Testing requirement analysis used normality test and homogeneity test. Data were analyzed by using the variance analysis. As a followed up of variance analysis, the post-hot test was conducted by using LSD test (Least Significant Difference). The result with α = 0,05 shows that (1) p = 0.00 < 0.05 that H0 is rejected which means that there is a difference of students’ learning achievement between students who taught by guided discovery method and the ones taught by expository method, and (2) p = 0.153 > 0.05 that H0 is accepted which means that there is no interaction between method and students’ learning motivation toward students’ learning achievement.